“Evaluación de la gestión administrativa y financiera de la corporación de mujeres Indígenas del cantón Guamote para fomentar su desarrollo organizacional”. - Vimos Parco, Jenny Rocío (2017)
Every social organization seeks to achieve its purposes with the efficient development of its management. Often, this is affected by internal factors such as a deferred administration, diversion of financial resources, lack of collaboration among its members, etc. The research was based on the existence of a problematic at both the administrative and financial levels, in order to develop clear and concise objectives that specify what it is desired to achieve and achieve. The theoretical framework summarizes the authors' criteria for titling work related to the study variables, as well as general aspects of the Indigenous Women's Corporation of Guamote obtained in the constitution and bylaws; An inquiry made to identify the structure, objectives, principles and aims that guide the organization. The state of the art also includes the detail of concepts related to administrative and financial management and organizational development, according to the criteria and approach of different authors. The methodology describes the deductive method, being its non-experimental design and its documentary and field type. Applying appropriate collection techniques, important data were obtained from the study variables, which, when analyzed and discussed, allowed to establish the reality of the administrative and financial management in the Guamote Indigenous Women's Corporation and how it has influenced organizational development.